The Role of Philanthropy in Women Development through Food Security - Makhubele, Thandi (University of the Witwatersrand, Johannesburg, 2022)
Food insecurity remains one of the critical issues for countries in the African continent. According to Pérez-Escamilla, (2017, p. 1), “food insecurity occurs when people do not have access to nutritious food and where food production is inadequate.” Most of the world’s rural population relies on agriculture for its livelihoods and to bolster their local economies (The World Bank Group, 2020). Small-scale farmers are the backbone of the agricultural sector in most rural areas. They (Small-scale farmers) provide access to food for vulnerable groups, including women and children (Misselhorn & Hendriks, 2017). Meanwhile women are the most affected by food insecurity, even though they are the main contributors to food production in most Sub-Saharan countries (Doss, 2018). Women in rural areas, in particular, rely on agriculture to fight food insecurity and to participate in local economies. In South Africa, small-scale women farmers ranked lowest in income accumulation, equal access to food production resources such as land and markets and financing (Sishuba, 2019). For this reason, government subsidies and philanthropic support are crucial for engaging women and assisting them with resources that can allow them to have equal access to land, resources, skills, and finances as their male counterparts. This research investigated the intersection between and among philanthropy, food security and women-owned initiatives in the agricultural sector in Limpopo. The study focuses on small- scale women farmers in the Vhembe and Capricorn districts in Limpopo, the two regions that are popular for large scale farming in South Africa. The research sought to answer the question; ‘what is the contribution of philanthropy to women development in the agriculture sector?’ A qualitative research approach was employed to explore the role of philanthropic organisations in women development, particularly in the agricultural sector in Limpopo. Two questionnaires through an online survey were used as the main methods to collect primary data . Forty seven (47) respondents were targeted. Of these, twenty four (24) were small scale farmers while twenty three (23) were drawn from philanthropic organisations operating in South Africa
A research report submitted in partial fulfillment of the requirements for the degree of Master of Management in the field of Security to the Faculty of Commerce, Law and Management, Wits School of Governance, University of the Witwatersrand, Johannesburg, 2022
Keywords: Food security; Development; Philanthropy; Food insecurity; Women; Agriculture; Small-scale farmers Gender; Support; Discrimination; UCTD; SDG-5: Gender equality